Optimierte Förderung von Elektrofahrzeugen als Schlüssel zur Erreichung nationaler Klimaziele - Helena Wisbert; Ann-Katrin Voit (Wirtschaftsdienst, 2025)
– The automotive sector plays a key role in achieving national climate targets. The transition to renewable energy and the transformation towards CO2-neutral individual mobility must therefore be continuously advanced. A government-funded special investment program of exteuro500 billion is planned to support infrastructure and climate protection investments in the coming years, with exteuro100 billion specifically allocated for climate protection measures. A central question arises: how can the available resources be utilised efficiently and effectively to address ecological, economic and social requirements equally? This study examines the impact of optimised incentives for battery electric vehicles (BEVs) based on the expired environmental bonus scheme of 2023, employing a scenario analysis of price elasticities across different price segments.
Keywords: Q48; H23; R41; 330